Thinking skills for secondary school students in Malaysia - Tee Tze Kiong, Md Yunos Jailani, Hassan Razali, Yee Mei Heong, Hussein Atan, Mohamad Mimi Mohaffyza (N/A, 2012)
Thinking skills for secondary school students in Malaysia by Tee Tze Kiong, Md Yunos Jailani, Hassan Razali, Yee Mei Heong, Hussein Atan, Mohamad Mimi Mohaffyza,